A meta-analysis of microarray datasets to identify biological regulatory networks in Alzheimer’s disease - Hashemi, Kimia Sadat; Aliabadi, Mohadese Koohi; Mehrara, Arian; Talebi, Elham; Hemmati, Ali Akbar; Rezaeiye, Radin Dabbagh; Ghanbary, Mohammad Javad; Motealleh, Maryam; Dayeri, Behnaz; Alashti, Shayan Khalili (Frontiers in Genetics, 2023)
Background: Alzheimer's Disease (AD) is an age-related progressive neurodegenerative disorder characterized by mental deterioration, memory deficit, and multiple cognitive abnormalities, with an overall prevalence of 2% among industrialized countries. Although a proper diagnosis is not yet available, identification of miRNAs and mRNAs could offer valuable insights into the molecular pathways underlying AD's prognosis.Method: This study aims to utilize microarray bioinformatic analysis to identify potential biomarkers of AD, by analyzing six microarray datasets (GSE4757, GSE5281, GSE16759, GSE28146, GSE12685, GSE1297) of AD patients, and control groups. Furthermore, this study conducted gene ontology, pathways analysis, and protein-protein interaction network to reveal major pathways linked to probable biological events. The datasets were meta-analyzed using bioinformatics tools, to identify significant differentially expressed genes (DEGs) and hub genes and their targeted miRNAs'.Results: According to the findings, CXCR4, TGFB1, ITGB1, MYH11, and SELE genes were identified as hub genes in this study. The analysis of DEGs using GO (gene ontology) revealed that these genes were significantly enriched in actin cytoskeleton regulation, ECM-receptor interaction, and hypertrophic cardiomyopathy. Eventually, and hsa-mir-9-3p exhibited significant interactions with most of the hub genes.Overall, these genes can be considered as pivotal biomarkers for diagnosing the pathogenesis and molecular functions of AD.